A Wideband Magnetic Frequency Up‐Converter Energy Harvester. Issue 6 (24th June 2021) - Fakeih, Esraa; Almansouri, Abdullah S.; Kosel, Jürgen; Younis, Mohammad I.; Salama, Khaled N.
Abstract : The cover illustrates a wideband mechanical energy harvester that utilizes street vibrations to power a traffic light. When this wideband harvester is placed in a vibrating environment, it converts the ambient vibrations into high‐voltage electrical energy. This energy can then be used to power various sensors and electronics. Further details can be found in the article, number 2001364, by Abdullah S. Almansouri, Khaled N. Salama, and co‐workers.